THE MODEL OF INDIVIDUAL PERFORMANCE IMPROVEMENT BASED ON STRENGTHENING OF HRM COMPONENTS INTERDEPENDENCE AT TOURISM INDUSTRY SMES - Hermawati, Adya -; Anam, Choirul; Suwarta, Suwarta (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Tourism industry small and medium enterprises need to be empowered to support the national economy. One proposed solution is improving individual performance of employees at these small and medium enterprises by strengthening the interdependence of three components of human resource management, namely innovative culture, quality of work life, and compensation. By this background, the objective of this research is to construct a model displaying this relationship. The research is done at 440 Tourism Industry SMEs in East Java Province involving 1320 employees as respondents chosen with a two-stage sampling procedure. Several results of research are obtained. Strong innovative culture creates a work environment that provides conditions that improve individual performance. A Highly innovative culture leads to a positive quality of work life. Work environment that allows employee participation and gives fair compensation would surely improve quality of work life. Fair compensation that is compatible with individual contribution would strengthen the relationship of both innovative culture and quality of work life with individual performance. Compensation that respects innovation and contribution of employees could impart better individual performance. All these results imply that individual performance could be improved by strengthening the interdependence of innovative culture, quality of work life and compensation that constitute human resource management.